2008
DOI: 10.1248/bpb.31.516
|View full text |Cite
|
Sign up to set email alerts
|

Functional Gene Cloning and Characterization of the SsmE Multidrug Efflux Pump from Serratia marcescens

Abstract: We cloned a gene responsible for multidrug resistance from chromosomal DNA of Serratia marcescens, and determined the nucleotide sequence. We designated the gene as ssmE. The deduced amino acid sequence of SsmE showed high similarity with the small multidrug resistance (SMR)-type multidrug efflux pumps. Cells of Escherichia coli KAM32, a drug hyper-susceptible mutant, transformed with a plasmid pESM437 carrying the ssmE gene showed elevated minimum inhibitory concentrations of structurally unrelated antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Overall, results demonstrated that AbeS could decrease susceptibility to some antibiotics, disinfectants, dyes, and detergents. The broad substrate specificity displayed by AbeS was very similar to those of other SMR transporters reported previously (6,14,16,17,34).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Overall, results demonstrated that AbeS could decrease susceptibility to some antibiotics, disinfectants, dyes, and detergents. The broad substrate specificity displayed by AbeS was very similar to those of other SMR transporters reported previously (6,14,16,17,34).…”
supporting
confidence: 85%
“…Reports show that 52% of currently sequenced genomes of eubacteria and archaea contain at least one SMR homologue (2). Well-studied examples of SMR efflux pumps include EmrE of Pseudomonas aeruginosa, EbrAB of Bacillus subtilis, SsmE of Serratia marcescens, and EmrE of Escherichia coli, which are involved in resistance to a variety of antimicrobial agents and quaternary ammonium compounds (14,16,17,34).…”
mentioning
confidence: 99%
“…fluoroquinolones (9). The amino acid at the equivalent position in SsmE is leucine as in wild-type EmrE.…”
Section: Isolation Of Mutants That Confer Resistance To Macrolides Andmentioning
confidence: 99%
“…The expression level of sugE in DFW9 was similar to that seen with ATCC 13047. In order to establish that SugE has the ability to extrude drugs from bacterial cells, we observed the efflux of ethidium from within preloaded cells by using a method described previously (14,15). KAM32/pSTV28 (control) and KAM32/ pSUGE28 cells carrying the sugE gene were tested.…”
Section: Fig 2 Hmentioning
confidence: 99%